USULAN DESAIN KEMASAN PRODUK ASAM JAWA DENGAN MENGGUNAKAN METODE KANSEI ENGINEERING Studi Kasus : Umkm Asam Jawa Jl. Pangeran Hidayat, Kec. Tembilahan - Annisa Annisa; Roberta Zulfhi Surya (JUTI UNISI, 2017)
Along with the development of increasingly complex era occurs the addition of functional values ​​and the role of packaging in marketing is recognized as a major force in market competition. Packaging has an important meaning in influencing consumers directly or indirectly in determining the choice of products to be purchased. Packaging performs many sales tasks ranging from attracting the attention of customers, describing the product to selling it. In this study the authors raised the title of Propose Design Packaging Asam Jawa products that will be authored by using the Kansei Engineering Method as the foundation. Kansei Engineering is a very suitable method for designing a packaging because this method is based on the feelings of consumers who buy and consume the product. The end result of the elimination process by Kansei Enggineering method is 5 cans and the percentage of influence on the design that will be applied in the design of Asam Jawa packaging that will be made; color is interesting, not tacky, bright and patterned as much as 12,4%, characteristic, character, memorable, unique, different with others as much as 14,4%, picture packing of acid picture, origin of food as much as 14,4%, informative, number phone manufacturer, net weight, expiration date, there is a composition, here is a brand as much as 25.2% and there is a halal code with as much as 8.4%. While the remaining 25.2% influenced by other factors. And based on the results of the questioner obtained an increase in the value of new Asam Jawa packaging made based on the engineering kansei method of 33,93% compared with the old packaging.